Interaksi dan Keterkaitan Spasial Wilayah di Kabupaten Penajam Paser Utara - Vidriza, Ullya (Jurnal Kajian Ekonomi dan Pembangunan, 2024)
Penajam Paser Utara Regency is one of the regions in East Kalimantan Province which will later be allocated as the “Ibu Kota Negara Indonesia” (IKN). This research aims to identify the central areas of growth and how these areas interact with each village in Penajam Paser Utara Regency. The analysis tools used are scalogram, centrality index, and gravity analysis. Based on the results of the scalogram analysis and centrality index, there are several growth center areas in Penajam Paser Utara Regency, there are Nipah-Nipah Village, Babulu Darat, Petung, Kampung Baru, Bukit Subur, Waru, Tengin Baru, Nenang, Sri Raharja, Sidorejo, Bukit Raya, Penajam, Lawe-Lawe, Bangun Mulya, Binuang, Sesumpu, Giripurwa, Sebakung Jaya, Riko, and Gunung Mulia. The gravity analysis results show that Petung Village has the strongest interaction with the Penajam Paser Utara area.